Plastic Optical Fiber as Water-Level Sensor - Waluyo, Bakti Dwi; Rambey, Joni Syafrin; Rahman S, Muhammad Aulia (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2023)
This research presents a low-cost sensor for measuring liquid levels using plastic optical fibers (POF). The sensor reduces the scattering-based optical losses in the fiber, which increase linearly with the liquid height. A U-bent fiber probe and photodetector are used to detect the change in optical intensity. The U-bent probe serves as a test probe for measuring the liquid level. The voltage response difference of the photodetector provides liquid level measurement. This study demonstrates the sensor's responsiveness to liquid level fluctuations above 55 cm at varying temperatures. Sensitivity levels of 1.4 and 3.3 mV/mm were achieved for water level fluctuations below and above 45 cm, respectively. Furthermore, the sensor demonstrated consistently stable responsiveness over multiple cycles.